2011
DOI: 10.1029/2011jb008379
|View full text |Cite
|
Sign up to set email alerts
|

The timing of strike-slip shear along the Ranong and Khlong Marui faults, Thailand

Abstract: [1] The timing of shear along many important strike-slip faults in Southeast Asia, such as the Ailao Shan-Red River, Mae Ping and Three Pagodas faults, is poorly understood. We present 40 Ar/ 39 Ar, U-Pb SHRIMP and microstructural data from the Ranong and Khlong Marui faults of Thailand to show that they experienced a major period of ductile dextral shear during the middle Eocene (48-40 Ma, centered on 44 Ma) which followed two phases of dextral shear along the Ranong Fault, before the Late Cretaceous (>81 Ma)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 84 publications
(137 reference statements)
0
27
0
Order By: Relevance
“…They measured Eocene crystallization ages from the Sedo granite, southeast of Mandalay, of 48.0 ± 0.9 and 53.8 ± 0.8 Ma. Further south, Watkinson et al (2011) reported Cretaceous SHRIMP U-Pb ages on zircons from both a weakly foliated tourmaline-muscovite-biotite porphyritic granite, a dominantly S-type mineralogy, and a more mylonitic granite. Both samples are sited within the Ranong Fault zone in southern Thailand (Fig.…”
Section: Neo-tethyan Overprint In the Western Marginal Beltmentioning
confidence: 96%
“…They measured Eocene crystallization ages from the Sedo granite, southeast of Mandalay, of 48.0 ± 0.9 and 53.8 ± 0.8 Ma. Further south, Watkinson et al (2011) reported Cretaceous SHRIMP U-Pb ages on zircons from both a weakly foliated tourmaline-muscovite-biotite porphyritic granite, a dominantly S-type mineralogy, and a more mylonitic granite. Both samples are sited within the Ranong Fault zone in southern Thailand (Fig.…”
Section: Neo-tethyan Overprint In the Western Marginal Beltmentioning
confidence: 96%
“…They measured zircon core ages of 214 ± 2 Ma and 212 ± 2 Ma, and Cretaceous zircon rim ages of 81.2 ± 2 Ma and 85-75 Ma respectively. Watkinson et al (2011) also reported Cretaceous SHRIMP U-Pb zircon ages of 81 to 70 Ma from granites exposed along the Ranong Fault zone in southern Thailand. We agree that Cretaceous ages measured at Doi Inthanon are part of a more regional magmatic and metamorphic overprint affecting Thailand and Myanmar, and further, we believe this is likely to be related to the eastwards subduction of Neo-Tethys under Sibumasu prior to the onset of the Himalayan Orogeny (e.g.…”
Section: Cretaceous Metamorphismmentioning
confidence: 99%
“…The Ranong and Khlong Marui shear zones in the southern Thailand extend from the continental margin and Mergui basin to the Gulf of Thailand from W to E (Tapponnier et al, 1986;Lacassin et al, 1997;Charusiri et al, 2002). All four major strike-slip shear zones in Thailand were probably active during the Eocene (Lacassin et al, 1997;Watkinson et al, 2011;Kanjanapayont et al, 2012b;Nantasin et al, 2012;Palin et al, 2013).…”
Section: Geological Settingmentioning
confidence: 99%